Experiential Processes in Narratives About Daily Situations Written by Primary Schools Students [Procesos Experienciales en Narraciones Sobre Situaciones Cotidianas Escritas por Escolares Básicos] - Rubio-Manriquez, M (Ediciones Universitarias de Valparaiso, 2019)
The purpose of this article is to describe the processes represented in finite clauses which are part of written narratives produced by elementary school students. In order to achieve this objective, verbs and verb phrases are analyzed as central elements in the configuration of experience, which is expanded by inherent participants in the represented process and circumstantial-type adjuncts. Clauses are considered the central process unit, as they convey the speakers choice in terms of the different systemic networks that are syntagmatically structured. The methodological approach corresponds to a quantitative description. The corpus presents a collection of 180 texts written by students in Grades 3, 5 and 7 attending one of two types of schools: a state school or a state-subsidized private school. The material processes that construct the experience as an external event, are significantly predominant in the corpus. However, such trend steadily decreases as students are promoted to the next grade, as evidenced by an increase of clauses with attributive and mental relational processes. It can be concluded that students describe concrete events from a perceptively external point of view, which tend to localize time and space. © 2019 PUCV, Chile.; El propósito de este artículo es describir los procesos representados en las cláusulas finitas que componen las narraciones escritas por escolares de educación básica. Para tal efecto, se analizan el verbo y los grupos verbales como elementos centrales en la configuración de la experiencia, núcleo que se expande con los participantes inherentes al proceso representado y con adjuntos de tipo circunstancial. Se considera la cláusula como unidad de procesamiento central, pues en ella se concretan las elecciones de los hablantes en diferentes redes sistémicas y se las estructura sintagmáticamente. El enfoque metodológico corresponde a una descripción cuantitativa. El corpus está compuesto por 180 textos escritos de escolares de 3°, 5° y 7° básicos de dos tipos de establecimiento escolares: uno municipal y uno particular subvencionado, con el fin de explorar si existen posibles diferencias. Se observa que en el corpus predominan los procesos materiales que conforman la experiencia como evento externo. No obstante, dicha tendencia va progresivamente disminuyendo a medida que se avanza en la escolaridad, pues aumenta la cantidad de cláusulas con procesos relacionales atributivos y cláusulas mentales. Se concluye que los escolares describen eventos concretos claramente perceptibles desde un punto de vista externo, los cuales tienden a localizar en el tiempo y el espacio. © 2019 PUCV, Chile.